ON CROSS REACTIONS OF EGG ALBUMIN SERA - Landsteiner, K. (The Rockefeller University Press, 1940)
Experiments are presented on the cross reactions of hen egg albumin immune sera with egg albumins of other species by means of exhaustion with heterologous proteins and by inhibition tests. From the results it can be concluded that the sera contain multiple, qualitatively distinct antibodies. For this, two not mutually exclusive explanations come into consideration: the presence in proteins of a number of different, perhaps similar, complex determinants, and the fact, established by previous results, that one antigenic grouping can call forth the formation of diverse antibodies. It is inferred that cross reactions between proteins of kindred species are ascribable, in general, to similarity in determinant structures, and not to the distribution of identical determinant groups among the related proteins.